Assessment of Instructional Strategies on Students’ Phobias and General Learning Difficulties in Senior Secondary Schools Mathematics - OLAREWAJU, Adijat Omoladun; Omotosho Jimoh SALIU; Murenikeji Alex AKANMU (Fakultas Pertanian, 2025)
Mathematics phobia and general learning difficulties continue to pose significant barriers to students’ achievement in Nigerian secondary schools. Given the importance of mathematics to both academic progression and future career opportunities, the persistence of these challenges is closely linked to the instructional approaches employed by teachers. This study examined the extent to which instructional strategies adopted by mathematics teachers influence students’ experiences of phobia and learning difficulties in senior secondary schools across Kwara State. The research adopted a descriptive survey design, with a sample comprising fifty purposively selected mathematics teachers and one hundred randomly chosen students from Ilorin East and West Local Government Areas. Data were gathered using a researcher-developed questionnaire that was validated and yielded a Cronbach's Alpha reliability coefficient of 0.75. Analysis of data through frequency counts and mean scores indicated that teachers made limited use of diverse instructional strategies (mean = 1.27, below the 1.50 benchmark). Results further showed that students exhibited high levels of mathematics-related phobia (weighted average = 2.28) and moderate-to-high levels of learning difficulties (weighted average = 2.21). The study recommends a pedagogical shift from conventional methods toward interactive strategies that integrate real-life contexts and technological applications, thereby making abstract ideas more concrete and reducing learner anxiety. The findings hold theoretical relevance for enriching discussions on instructional reform in mathematics education and practical significance for guiding teachers toward practices that encourage positive dispositions and enhance performance among students.